Information and Communication Technology for Sustainable Development Proceedings of ICT4SD 2016, Volume 1 - Mishra, Durgesh Kumar; Nayak, Malaya Kumar; Joshi, Amit.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
The book proposes new technologies and discusses future solutions for design infrastructure for ICT. The book contains high quality submissions presented at Second International Conference on Information and Communication Technology for Sustainable Development (ICT4SD - 2016) held at Goa, India during 1 - 2 July, 2016. The conference stimulates the cutting-edge research discussions among many academic pioneering researchers, scientists, industrial engineers, and students from all around the world. The topics covered in this book also focus on innovative issues at international level by bringing together the experts from different countries.
Preface -- About the editors -- Conference Organising Committee -- Chapters -- Author Index.
Keywords: Computational intelligence; Data mining; Computer-aided engineering; Telecommunication; Computational Intelligence; Data Mining and Knowledge Discovery; Computer-Aided Engineering (CAD, CAE) and Design; Communications Engineering, Networks